The time of literacy in Ceará: The PAIC and the multiple streams model - Sumiya, Lilia Asuca; Araújo, Maria Arlete Duarte; Sano, Hironobu (Education Policy Analysis Archives, 2017)
This study aims to understand how the issue of illiteracy became prominent on the agenda of Ceara’s state government, in Brazil, by analyzing the formulation of the Literacy Program at the Right Age (PAIC). Tracing the origin of the program and applying Kingdon’s (1995) multiple streams model, the study identifies the elements of problems, politics and public policy streams. This research adopts a qualitative approach and is based on a single case study method. The data set consisted of institutional PAIC-related documents, tachygraphy notes from sessions held at the Ceará’s State House of Representatives, press clippings, academic studies and interviews with key participants from several organizations. A combination of factors influenced the formulation of the literacy policy, and particularly relevant are the actions of the policy entrepreneur, the processes of problem recognition for the composition of a wide coalition, and the process of alternative specification. Finally, the results suggest that the applicability of the multiple streams approach is a useful analytical tool, and it contributes to better understanding of policy formation in the Brazilian educational field.